2017
DOI: 10.1038/s41598-017-13454-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial glycerol 3-phosphate facilitates bumblebee pre-flight thermogenesis

Abstract: Bumblebees (Bombus terrestris) fly at low ambient temperatures where other insects cannot, and to do so they must pre-warm their flight muscles. While some have proposed mechanisms, none fully explain how pre-flight thermogenesis occurs. Here, we present a novel hypothesis based on the less studied mitochondrial glycerol 3-phosphate dehydrogenase pathway (mGPDH). Using calorimetry, and high resolution respirometry coupled with fluorimetry, we report substrate oxidation by mGPDH in permeabilised flight muscles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 42 publications
0
25
1
Order By: Relevance
“…This is true for bumble bees, especially in montane regions (Hines & Williams, ; Martinet et al, ; Williams, ; Williams et al, ). Facultative endothermy makes bumble bees well suited for low temperatures, with several mechanisms to generate heat that include activation of muscles for nonflight thermogenesis (“shivering”) (Esch & Goller, ; Heinrich, ; Heinrich & Kammer, ; Masson, Hedges, Devaux, James, & Hickey, ). In insects generally, loss of neuromuscular function at cold temperatures can lead to the loss of coordinated movement and, ultimately, “chill coma” (Kelty & Lee, ; MacMillan & Sinclair, ; Overgaard & MacMillan, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is true for bumble bees, especially in montane regions (Hines & Williams, ; Martinet et al, ; Williams, ; Williams et al, ). Facultative endothermy makes bumble bees well suited for low temperatures, with several mechanisms to generate heat that include activation of muscles for nonflight thermogenesis (“shivering”) (Esch & Goller, ; Heinrich, ; Heinrich & Kammer, ; Masson, Hedges, Devaux, James, & Hickey, ). In insects generally, loss of neuromuscular function at cold temperatures can lead to the loss of coordinated movement and, ultimately, “chill coma” (Kelty & Lee, ; MacMillan & Sinclair, ; Overgaard & MacMillan, ).…”
Section: Discussionmentioning
confidence: 99%
“…This is true for bumble bees, especially in montane regions (Hines & Williams, 2012;Martinet et al, 2018;Williams, 1985;Williams et al, 2018). Facultative endothermy makes bumble bees well suited for low temperatures, with several mechanisms to generate heat that include activation of muscles for nonflight thermogenesis ("shivering") (Esch & Goller, 1991;Heinrich, 1975;Heinrich & Kammer, 1973;Masson, Hedges, Devaux, James, & Hickey, 2017). In insects generally, loss of neuromuscular function at cold temperatures can lead to the loss of coordinated movement and, ultimately, "chill coma" (Kelty & Lee, 2001;MacMillan & Sinclair, 2011;Overgaard & MacMillan, 2017 Path encoding genes in D. melanogaster (e.g., the LOC100747727-LOC100747447 region with beat-III, LOC100746249 and a second gene LOC100740312 with sidestep genes), which is worth further investigation because these proteins directly interact at the motor neuron synapse (Arzan Zarin & Labrador, 2019;Carrillo et al, 2015;Inaki, Yoshikawa, Thomas, Aburatani, & Nose, 2007;Li et al, 2017;Pipes, Lin, Riley, & Goodman, 2001).…”
Section: Temperaturementioning
confidence: 99%
“…Earlier it was shown that bumblebees are able to survive at slightly subzero temperatures (Owen, Bale, & Hayward, ), which allows them not to hibernate and retain the ability to pollinate in wintertime in southern UK, as previously described by Stelzer, Chittka, Carlton, and Ings, . It has been suggested that B. terrestris are capable to active flight at slightly below subzero temperatures due to the increased activity of mitochondrial glycerol‐3‐phosphate dehydrogenase (mGPDH; Masson et al, ), since this enzyme is less sensitive to temperature changes compared to other metabolic enzymes. In addition, the usage of α‐glycerophosphate as a substrate for respiration is associated with low ETC energizing.…”
Section: Discussionmentioning
confidence: 91%
“…The role of high respiration rate of α‐glycerophosphate in A. mellifera flight muscles mitochondria is not completely understood, because the oxidation of this substrate is not associated with the production of ATP (Soares et al, ). It is unlikely that the high rate of oxidation of α‐glycerophosphate has a thermogenesis function similar to B. terrestris (Masson, Hedges, Devaux, James, & Hickey, ). For this reason, the study of the biological role of α‐glycerophosphate oxidation in A. mellifera flight muscles mitochondria needs further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation